2014
DOI: 10.1186/2049-1891-5-35
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression estimator of intramuscular fat percentage for use in both cattle and sheep

Abstract: BackgroundThe expression of genes encoding proteins involved in triacyglyceride and fatty acid synthesis and storage in cattle muscle are correlated with intramuscular fat (IMF)%. Are the same genes also correlated with IMF% in sheep muscle, and can the same set of genes be used to estimate IMF% in both species?ResultsThe correlation between gene expression (microarray) and IMF% in the longissimus muscle (LM) of twenty sheep was calculated. An integrated analysis of this dataset with an equivalent cattle corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 24 publications
2
41
0
2
Order By: Relevance
“…The ACLY gene, which encodes ATP citrate lyase and is associated with the tricarboxylic acid cycle, might help to sustain the lipogenic process (Graugnard et al, 2010). In addition, the expression of ACLY has been strongly correlated with intramuscular fat in sheep and cattle (Guo et al, 2014). Davoli et al (2014) investigated two SNPs in the porcine ACLY gene and found significant associations between polymorphisms and the productive traits average daily gain, ham weight, and back fat thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACLY gene, which encodes ATP citrate lyase and is associated with the tricarboxylic acid cycle, might help to sustain the lipogenic process (Graugnard et al, 2010). In addition, the expression of ACLY has been strongly correlated with intramuscular fat in sheep and cattle (Guo et al, 2014). Davoli et al (2014) investigated two SNPs in the porcine ACLY gene and found significant associations between polymorphisms and the productive traits average daily gain, ham weight, and back fat thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have focused on ACLY polymorphisms and their association with growth and carcass quality traits in pig (Muรฑoz et al, 2013;Davoli et al, 2014). In addition, the expression of ACLY is associated with intramuscular fat percentage in sheep (Guo et al, 2014). However, studies investigating the association of polymorphisms with growth traits in beef cattle in northwest China are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxytryptamine) is a hormone that plays a role in reproductive functions in mammals [33], particularly in the growth and maturation of oocytes in the ovary and steroidogenesis in the granulosa cells via the mitogen-activated protein kinase pathway [10,34]. Melatonin is also essential for the function of the circadian clock that influences activity and sleep [31,35]. The mechanism by which melatonin regulates reproduction has been reported to be through the control of gonadotropin releasing hormone (GnRH) and gonadotropin inhibiting hormone (GnIH) receptors primarily found in the hypothalamic-pituitary axis to release gonadotropin hormones [11,33,36].…”
Section: Aanatmentioning
confidence: 99%
“…G0S2 ์œ ์ „์ž๋Š” ๋‹ค๋ฅธ ์—ฐ๊ตฌ์—์„œ ์†Œ์˜ ์ง€๋ฐฉ์‚ฐ ์ถ•์  ๊ณผ ์ง€๋ฐฉ์‚ฐ ๋Œ€์‚ฌ์— ๊ด€๋ จ์„ฑ์„ ๋ณด์ด๋Š” ํ›„๋ณด์œ ์ „์ž๋กœ ๋ณด๊ณ ๋œ๋ฐ” ์žˆ๋‹ค (Zhao et al, 2012;Guo et al, 2014 (Nadaf et al, 2007) (Table 1). GGA2์—์„œ ๋Š” 119โˆผ153, 380.3 cM ์˜์—ญ์—์„œ 2๊ฐœ์˜ QTL์ด ํ™•์ธ๋˜์—ˆ๊ณ , ์ด ์ค‘์—์„œ 380.3 cM ์˜์—ญ์˜ QTL์€ sex-specificํ•œ suggestive QTL๋กœ ํ™•์ธ๋˜์—ˆ๋‹ค (Wright et al, 2006;Nadaf et al, 2007) (Table 1).…”
Section: Zeng Et Al(2011)์€ Xinghua์™€ Recessive White Leghorn์„unclassified